Palladium-catalyzed direct γ-C(sp3)–H arylation of β-alkoxy cyclohexenones: reaction scope and mechanistic insights. Issue 9 (25th February 2022) - Shao, Li-Dong; Chen, Yang; Wang, Mei; Xiao, Nan; Zhang, Zhi-Jun; Li, Dashan; Li, Rong-Tao
Abstract : Direct γ-C(sp 3 )-arylation of unactivated electron-rich enones remains a challenge. We have found a Pd-catalyzed method for direct γ-C(sp 3 )-arylation of unactivated β-alkoxy cyclohexenones which enables the synthesis of bioactive CBD-like compounds. Abstract : The direct γ-C(sp 3 )-arylation of unactivated electron-rich enones has been a long-standing challenge. Herein, a mild Pd-catalyzed method for direct γ-C(sp 3 )-arylation of various unactivated β-alkoxy cyclohexenones is reported. The method is not only tolerated well with many ortho -hetero substituted aryl bromides but also with the sterically hindered ortho -dimethoxy or rigid ortho -diaryl aryl bromides. Mechanistic studies suggest the tunneling is likely to govern the [1, 5]-H shift of the α′-dienolate-PdArL intermediate and consequently forms the γ-arylated product, therefore exhibiting an excellent γ-site selectivity. Finally, our method enables the facile synthesis of CBD-like compounds with selective anti-proliferative effects against glioma stem cells.